TRANSYLVANIAN ECHOES OF THE UNION OF THE ROMANIAN PRINCIPALITIES - Mihai D. DRECIN (Annals: Series on History and Archaeology (Academy of Romanian Scientists), 2022)
Based on documents and published literature, we will show how the Union of the Romanian Principalities in 1859 and the figure of the ruler Alexandru Ioan Cuza had echoes in Bihor and Maramureș, two Romanian areas in Western Transylvania which were subjected to a ruthless process of Hungarianization before 1918. It should be noted that the political event of 1859 and, above all, the figure of Alexandru Ioan Cuza, had lasting influences well after 1866, both in the lives of ordinary Romanians and in those of the cultural, religious and political elites. The examples provided by us will support the view that has been already established in our country’s ancient and modern historiography, according to which the pre-modern and modern times served as a consistent and sound foundation for the creation of Greater Romania in 1918, from a social, economic, cultural, political and moral perspective.